2011
DOI: 10.1021/cb200351y
|View full text |Cite
|
Sign up to set email alerts
|

Cellobiose Dehydrogenase and a Copper-Dependent Polysaccharide Monooxygenase Potentiate Cellulose Degradation by Neurospora crassa

Abstract: The high cost of enzymes for saccharification of lignocellulosic biomass is a major barrier to the production of second generation biofuels. Using a combination of genetic and biochemical techniques, we report that filamentous fungi use oxidative enzymes to cleave glycosidic bonds in cellulose. Deletion of cdh-1, the gene encoding the major cellobiose dehydrogenase of Neurospora crassa, reduced cellulase activity substantially, and addition of purified cellobiose dehydrogenases from M. thermophila to the Δcdh-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
816
1
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 601 publications
(846 citation statements)
references
References 34 publications
17
816
1
12
Order By: Relevance
“…Although CBM33-type and GH61-type LPMOs seem to catalyze essentially the same reaction (4,5,12,13,23) and have similar active sites ( Fig. 1 D and E), their metal binding sites do show some notable differences.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although CBM33-type and GH61-type LPMOs seem to catalyze essentially the same reaction (4,5,12,13,23) and have similar active sites ( Fig. 1 D and E), their metal binding sites do show some notable differences.…”
Section: Discussionmentioning
confidence: 98%
“…1). The identity of the metal was not disclosed in early work (5,10), but functional studies on related enzymes, a CBM33 from Enterococcus faecalis (11) and three GH61s (4,12,13), have later indicated that the LPMOs are copper-dependent enzymes. However, because of several complications, such as the indiscriminate nature of the metal binding site (see below) and the fact that the CBM33 crystal structures obtained so far mostly were metal-free, many aspects of metal binding remain unresolved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that in a recently published study by Isaksen et al (38), hydrogen peroxide formation, by a Cu-AA9 enzyme with different reductants and O 2 , was detected only in the absence of substrate or with substrates that were not subject to AA9 activity. If the superoxide is indeed stabilized by the substrate, it may be able to directly attack the polysaccharide, or it may be further reduced to a more reactive species by either small molecules or cellobiose dehydrogenase (a known AA9 reducing cofactor) (7,13,39). This awaits further experimental investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a class of oxygen activating enzymes with a single copper center has been identified, the polysaccharride monooxygenases [PMOs; often termed lytic polysaccharide monooxygenases (LPMOs), reflecting their ability to break polysaccharides chains and loosen crystalline structure] (6-8), or AA9 to 11 enzymes (AA = auxiliary activity) in the Carbohydrate-Active enZYmes (CAZy) database (9). AA9 enzymes [formerly glycoside hydrolases family 61 (GH61s)] are fungal enzymes that can enhance major cellulases' enzymatic degradation of cellulose (hence "auxiliary activity"), whereas AA10 enzymes [formerly carbohydrate binding module family 33 (CBM33)] are predominantly bacterial enzymes that can enhance major chitinases' degradation of chitin (6,7,(10)(11)(12)(13). Enzymes in the latest discovered subclass, AA11, are fungal enzymes, where the currently lone characterized example uses chitin as a substrate (8).…”
mentioning
confidence: 99%